MODERATION-BASED LEARNING DESIGN: INOVASI MODEL PEMBELAJARAN MODERASI BERAGAMA DALAM MENCEGAH RADIKALISME SISWA - Fawrina Amilus Shalihah; Muhammad Mushfi El Iq Bali (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study aims to analyze and formulate a religious moderation learning model as a preventive strategy against cognitive radicalism in Madrasah  Tsanawiyah students ,the study was conducted at Mts Negeri 2 situbondo which has a pluralistic and dynamic socio-religious backgrond ,making it relevant as an empirical context for the study.the approach used was a qualitative case study ,using data collection technigues such as classroom observations ,in -depth interviews with islamic Religious Education teachers and learning documentation .data analysis was carried out interactively througt data reducction ,data presentation ,and drawing conclusions using a reflective -critical approach .the results of the study indicate that an effective religious moderation learning model in preventing cognitive radicalism is dialogic, contextual, and teacher-exemplary learning. This strategy is realized through the integration of  moderation values ​in teaching materials, the use of reflective discussion methods, and the linking of religious teachings with social and national realities. In addition, the role of teachers as role models has been proven to have a significant influence in shaping inclusive and tolerant religious attitudes. This study also found that a pedagogical approach that emphasizes the development of critical awareness in students is able to suppress the tendency to think exclusively and absolutistically. Thus, religious moderation is understood not only as a normative value, but as a systematic and replicable operational pedagogical practice. These findings provide theoretical and empirical contributions to the development of moderate Islamic education that is adaptive to the challenges of radicalism in educational settings